Shallow Lake Economics Run Deep: Nonlinear Aspects of an Economic-Ecological Interest Conflict - F.O.O. Wagener (Tinbergen Institute, 2009)
Outcomes of the shallow lake interest conflict are presented in a number of different contexts: quasi-static and dynamic social planning, and quasi-static one-shot and repeated non-cooperative play. As the underlying dynamics are non-convex, the analysis uses geometrical-numerical methods: the possible kinds of solutions are efficiently classified in bifurcation diagrams.
Keywords: C61; C73; Q57; 330; Shallow lake; optimal management; dynamic games; bifurcation analysis; Gewässerschutz; Sozialer Konflikt; Dynamisches Spiel; Mathematische Optimierung; Nichtlineare dynamische Systeme; Theorie